La mise en scène d’un procès pénal : réflexion sur les médias et le procès Demjanjuk - Rainer Volk (Criminocorpus)
The criminal trial of John (Ivan) Demjanjuk, which began on 30 November 2009 and ended in May 2011, was considered to be the last criminal trial against Holocaust perpetrators. The media interest in the courtroom was correspondingly high. However, the essay shows that this interest had its ups and downs. It also highlights the fact that much of the media coverage was limited to the dramatic circumstances of the case, while less attention was paid to the gaps in the evidence, which historians consider problematic. However, the court find the defendant guilty, which also raises the question of whether the Demjanjuk trial was intended to make up - very late in the day - for the German justice systems’ failure to deal with Nazi crimes.